Methacrylate copolymer, method for producing photoresist composition, and use thereof
Patent Information
- Application Number
- CN202611079489.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-21
AI Technical Summary
物理共混体系的固有相容性问题:传统酚醛树脂与DNQ感光剂仅通过物理方式混合,二者相容性较差,长期储存易发生相分离,导致光刻胶均匀性下降、感光度波动;同时感光基团分布不均匀,易造成显影后图形边缘粗糙、分辨率降低,难以满足高世代线的生产要求;常规的(甲基)丙烯酸酯类树脂,虽然可以通过引入苯基、环烷基或羟基等基团来分别改善耐热性或附着力,但其性能优化往往依赖于复杂的物理共混与配方调整;这种补丁式的改进通常导致材料性能仅在一个非常狭窄的工艺参数(如后烘温度、显影时间)窗口内达到最佳,工艺参数的微小波动极易引起图案缺陷(如侧壁倾斜、底部钻蚀或残留),严重影响了大规模生产的良率和稳定性
将感光基团通过化学键合方式接入聚合物侧链,其光敏性优于采用物理共混方式制备得到的正性光刻胶组分;本发明通过特定单体配比与侧链结构协同作用,使光刻胶在2.38% TMAH显影液中能获得更宽的工艺窗口,显影窗口在60 s以上;同时本发明提供的正性光刻胶组合物在热失重分析中,总质量损失5%(Td5%)时的温度均高于276℃、透光率大于93%、折射率不低于1.53、耐干蚀刻性均小于0.98 μm。
Smart Images

Figure CN122587111B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing and applying a methacrylate copolymer and photoresist composition, belonging to the field of photoresist technology. Background Technology
[0002] Photoresist is a core material for transferring fine patterns in microelectronics manufacturing and flat panel display industries, and its performance directly determines the resolution, yield, and reliability of devices. Positive photoresists, due to their advantages such as high resolution, good contrast, and strong process compatibility, dominate the fabrication of array substrates, color filters, and organic insulating layers in thin-film transistor liquid crystal displays (TFT-LCDs). Currently, the most widely used positive photoresists in industry are phenolic resin-diazonaphthoquinone (DNQ) physical blend systems. In this system, diazonaphthoquinone compounds act as photosensitizers, undergoing Wolf rearrangement under ultraviolet light irradiation to generate indanone carboxylic acid, thereby creating a difference in solubility between exposed and unexposed areas in alkaline developing solutions.
[0003] As TFT-LCDs develop towards higher resolution, higher brightness, and narrower bezels, more stringent comprehensive performance requirements are placed on photoresists used in organic insulating layers: they not only need to have excellent photosensitivity and a wide development process window, but also need to simultaneously meet the requirements of high thermal stability (to withstand subsequent high-temperature evaporation and annealing processes), high light transmittance (to reduce light loss), high refractive index (to reduce interface reflection), and good resistance to dry etching (to ensure pattern transfer accuracy).
[0004] However, existing photoresist systems still suffer from the following insurmountable drawbacks: The inherent compatibility issues of physically blended systems: Traditional phenolic resins and DNQ photosensitizers are mixed only physically, resulting in poor compatibility. Long-term storage can easily lead to phase separation, causing a decrease in photoresist uniformity and fluctuations in photosensitivity. At the same time, uneven distribution of photosensitive groups can easily cause rough edges and reduced resolution of the pattern after development, making it difficult to meet the production requirements of high-generation lines. Although conventional (meth)acrylate resins can improve heat resistance or adhesion by introducing phenyl, cycloalkyl, or hydroxyl groups, their performance optimization often depends on complex physical blending and formulation adjustments. This patch-like improvement usually results in the material performance reaching its optimal state only within a very narrow process parameter window (such as post-baking temperature and development time). Small fluctuations in process parameters can easily cause pattern defects (such as sidewall tilting, bottom etching, or residue), seriously affecting the yield and stability of large-scale production. Furthermore, when forming thicker organic insulating films, conventionally physically blended photosensitizers (such as diazonoquinones) are prone to uneven light absorption distribution, leading to insufficient bottom exposure and the formation of non-ideal trapezoidal cross-sections rather than vertical sidewalls. For example, the published patent KR1020040032468A achieves a balance in heat resistance, adhesion, light transmittance, and pattern verticality by proportioning two adhesive resins, photosensitizers, and silicon-based compounds. However, this approach relies on the precise synergy of a multi-component system, and its complexity poses significant challenges to process control and batch stability in large-scale production, increasing the uncertainty of industrialization. Similarly, Chinese patent CN108535960B improves heat resistance through a simple method of physically blending heat-resistant resin into phenolic resin. However, this method does not change the chemical nature of the main resin, limiting the improvement in heat resistance and having a limited effect on widening the development process window, making it difficult to meet the requirements of advanced processes at higher temperatures.
[0005] The performance of chemically grafted photoresists is insufficient: In order to solve the compatibility problem, existing research attempts to attach photosensitive groups to the polymer backbone or side chain through chemical bonding. For example, Chinese patent CN119930894B discloses a PAG-bonded photosensitive photoresist resin and its preparation method and application. The invention obtains the PAG-bonded resin through the following reaction process: (1) p-acetoxystyrene, p-styrenesulfonylimide trifluoromethyl potassium salt and RAFT chain transfer agent undergo RAFT polymerization reaction under the action of an initiator to obtain intermediate I; (2) intermediate I undergoes hydrolysis reaction to obtain intermediate II; (3) intermediate II reacts with the introduced protecting group of ditert-butyl dicarbonate to obtain intermediate III; (4) intermediate III undergoes ion exchange reaction with triphenylsulfonium bromide. However, existing chemically grafted photoresists generally have the problems of complex monomer synthesis routes and poor copolymerization controllability, and it is difficult to achieve a balance between thermal stability and solubility at the same time.
[0006] Existing technologies have narrow development process windows (usually less than 40 seconds), are extremely sensitive to fluctuations in development time and temperature, have low process tolerance, and cannot adapt to large-scale industrial production.
[0007] Key performance indicators are difficult to balance: existing positive photoresists for TFT-LCDs are subject to mutual constraints in terms of thermal stability, optical performance, and etching resistance.
[0008] For example, introducing rigid groups to improve thermal stability often leads to decreased solubility and increased residual adhesive after development; while pursuing high light transmittance usually sacrifices refractive index and resistance to dry etching.
[0009] Therefore, how to develop a positive photoresist composition that combines excellent photosensitivity, wide development window, high thermal stability, high optical performance, and good etch resistance is a technical problem that the flat panel display industry urgently needs to solve. Summary of the Invention
[0010] To obtain a positive photoresist composition with excellent photosensitivity, wide development window, high thermal stability, high optical performance and good etch resistance, this invention provides a method for preparing a methacrylate copolymer and a photoresist composition, as well as its application.
[0011] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: A photosensitive monomer, the structure of which is shown in formula (II):
[0012] II In formula (II), R1 is independently selected from one of hydrogen atoms, alkyl derivatives and phenyl derivatives; X is independently selected from either oxygen or sulfur atoms; R5 is independently selected from one of hydrogen atoms, C1-C8 alkyl groups, C3-C8 cycloalkyl derivatives, phenyl groups, phenyl derivatives, and the group -X-R6; R6 is independently selected from one of the following structures: .
[0013] The present invention also provides stereoisomers, geometric isomers, tautomers, enantiomers and diastereomers of the above-mentioned photosensitive monomers.
[0014] The present invention also provides the application of the above-mentioned photosensitive monomer in the preparation of photoresist.
[0015] The present invention also provides a method for preparing the above-mentioned photosensitive monomer, comprising the following steps: (1) Dissolve phenolic substituted styrene and diazonoquinone, mix with non-metallic ion bases to obtain intermediate reactants; (2) Mix the intermediate reactant obtained in step (1) with the halogen-free acid, and separate them to obtain the final product; The phenolic substituted styrene is selected from one of p-hydroxystyrene, o-hydroxystyrene, m-hydroxystyrene, 4-vinylguaiacol, 3,4-dihydroxystyrene, 1,3-dihydroxystyrene, 4,4'-(ethylene-1,1-diyl)diphenol, eugenol, p-hydroxycinnamic acid, 4,4'-dihydroxystyrene, 4,4'-dihydroxystyrene derivatives, p-mercaptostyrene, and p-mercaptostyrene derivatives.
[0016] Preferably, the molar ratio of the phenolic substituted styrene, diazonaphthoquinone, and non-metallic ion base is 1:1-1.1:1-1.1.
[0017] Preferably, the diazonoquinone raw material is selected from one or both of 2-diazo-1-naphthol-5-sulfonyl chloride and 2-diazo-1-naphthol-4-sulfonyl chloride.
[0018] Preferably, the non-metallic ionic base is selected from one or more of amine compounds and nitrogen-containing heterocyclic compounds.
[0019] More preferably, the amine compound is selected from the following range: methylamine, ethylamine, trimethylamine, triethylamine, and tetramethylamine hydroxide; The range of nitrogen-containing heterocyclic compounds to be selected is pyridine and imidazole.
[0020] Preferably, the halogen-free acid is selected from one or more of sulfuric acid, nitric acid, phosphoric acid, formic acid, acetic acid, propionic acid, oxalic acid, and malonic acid.
[0021] Preferably, the separation method in step (2) includes the anti-solvent method; The antisolvent used in the aforementioned antisolvent method is water.
[0022] More preferably, the temperature of the antisolvent method is -20 to 80°C.
[0023] More preferably, the temperature of the antisolvent method is -10 to 70°C.
[0024] More preferably, the temperature of the antisolvent method is 10-40°C.
[0025] More preferably, the volume ratio of the antisolvent to the solvent system of the reactants to be separated in the antisolvent method is 5-100:1.
[0026] More preferably, the antisolvent method further includes a filtration step.
[0027] More preferably, the separation method further includes a step of washing the separated material until it is neutral.
[0028] The present invention also provides a methacrylate copolymer with the structure shown in formula (I):
[0029] Ⅰ In formula (Ⅰ), X is independently selected from either oxygen or sulfur atoms; R1 is independently selected from one of hydrogen atoms, alkyl derivatives, and phenyl derivatives; R2 is independently selected from one of carboxyl, acid anhydride, C1-C8 alkyl, C1-C8 alkyl derivative, C3-C18 cycloalkyl, C3-C18 cycloalkyl derivative, phenyl and phenyl derivative; R3 is independently selected from one of hydrogen atoms, C2-C8 alkyl groups, C2-C8 alkyl derivatives, C3-C18 cycloalkyl derivatives, phenyl groups, and phenyl derivatives; R4 is independently selected from either a hydrogen atom or a methyl group; R5 is independently selected from one of the following: hydrogen atom, C1-C8 alkyl group, C1-C8 alkyl derivative, C3-C18 cycloalkyl group, C3-C18 cycloalkyl derivative, phenyl group, phenyl derivative, and group -X-R6; R6 is independently selected from one of the following structures:
[0030] In terms of molar ratio, a:b:c = 0-1:0-1:0-1, and a, b, and c are not all 0 at the same time.
[0031] Preferably, the methacrylate copolymer has a weight-average molecular weight of 2000-20000 and a dispersion of 1.0-3.0.
[0032] Preferably, the acid value of the methacrylate copolymer is 40-140 mgKOH / g.
[0033] More preferably, the acid value of the methacrylate copolymer is 50-130 mgKOH / g.
[0034] More preferably, the acid value of the methacrylate copolymer is 60-120 mgKOH / g.
[0035] The present invention also provides a method for preparing the above-mentioned methacrylate copolymer, comprising the following steps: S1. Dissolve the copolymer monomer in propylene glycol monomethyl ether acetate to obtain a monomer solution; S2. Mix the monomer solution obtained in step S1 with the initiator to react and obtain the product to be separated; S3. Separate the product to be separated obtained in step S2 to obtain the methacrylate copolymer; The copolymer monomer is selected from one or more of the following: general formula (II) photosensitive monomers, (meth)acrylic acid, (meth)methyl acrylate, (meth)ethyl acrylate, (meth)propyl acrylate, (meth)butyl acrylate, (meth)pentyl acrylate, (meth)hydroxyethyl acrylate, (meth)hydroxypropyl acrylate, (meth)hydroxybutyl acrylate, (meth)glycidyl acrylate, (meth)benzyl acrylate, styrene, styrene derivatives, vinyl acetate, (meth)adamantyl acrylate and (meth)adamantyl acrylate derivatives;
[0036] II In formula (II), R1 is independently selected from one of hydrogen atoms, alkyl derivatives and phenyl derivatives; X is independently selected from either oxygen or sulfur atoms; R5 is independently selected from one of hydrogen atom, C1-C8 alkyl, C3-C8 cycloalkyl derivative, phenyl, phenyl derivative and group -X-R6; R6 is independently selected from one of the following structures, .
[0037] Preferably, the initiator is selected from one or more photoinitiators and thermal initiators; The range of photoinitiators selected includes: α-aminoketones, oxime esters, acylphosphine oxides, benzophenones, and triazine photoinitiators.
[0038] The range of thermal initiators to be selected includes: azo thermal initiators, organic peroxide thermal initiators, and inorganic peroxide thermal initiators.
[0039] More preferably, the photoinitiator is selected from the following range: photoinitiator 369, photoinitiator 907, triarylsulfonium hexafluoroantimonate mixture (CAS: 109037-75-4), 4-isobutylphenyl-4'-methylphenyliodonium hexafluorophosphate (CAS: 344562-80-7), benzophenone, 1-hydroxy-1-phenylcyclohexane, benzyl dimethyl ketone, 1-benzyl-1-dimethylamino-1-(4-pentadienylphenyl ketone)propane, 2-pentadienyl-2-(4-methyl methacrylate)phenylpropane, isopropoxyphenylacetone, diethoxyphenylacetone, ethoxyphenylacetone, diphenyl(2,4,6) -trimethylbenzoyl)-phosphonate, 10-butyl-2-chloramine, 4,4'-di(diethylamino)-benzophenone, 2-[2-(4-methoxy-benzene)-ethylene]-4,6-di-trichloromethyl-[1,3,5]triazine, 2-(4-methyl-naphthyl-1-yl)-4,6-trichloromethyl[1,3,5]trichloromethane, 2-benzo[1,3]dioxacyclopenten-5-yl-4,6-trichloromethyl[1,3,5]triazine, 2-methyl-4,6-di(trichloromethyl)-s-triazine, 2-benzene-4,6-di(trichloromethyl)-s-triazine, 2-naphthyl-4,6-di(trichloromethyl)-s-triazine; The range of thermal initiators to be selected is: azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, and potassium persulfate.
[0040] Preferably, the mass ratio of the photosensitive monomer represented by the general formula (II) structure to the methacrylate copolymer represented by the general formula (I) is 0-25%.
[0041] More preferably, the mass ratio of the photosensitive monomer represented by the general formula (II) structure to the methacrylate copolymer represented by the general formula (I) is 1-20%.
[0042] More preferably, the mass ratio of the photosensitive monomer represented by the general formula (II) structure to the methacrylate copolymer represented by the general formula (I) is 5-17%.
[0043] Preferably, the copolymer monomer content in the monomer solution is 20% by mass.
[0044] Preferably, the mass amount of the initiator is 0.1-10% of the total amount of copolymer monomers.
[0045] Preferably, the reaction temperature in step S2 is 40-120°C, and the reaction time is 4-72 h.
[0046] More preferably, the reaction temperature is 50-100℃ and the reaction time is 5-48 h.
[0047] More preferably, the reaction temperature is 55-90°C and the reaction time is 6-24 h.
[0048] Most preferably, the reaction temperature is 80°C and the reaction time is 8-12 h.
[0049] The present invention also provides the application of the above-mentioned methacrylate copolymer in the preparation of photoresists.
[0050] The present invention also provides a positive photoresist composition comprising the above-mentioned methacrylate copolymer, comprising the following raw material components in parts by weight: 100 parts methacrylate copolymer, 0-10 parts photosensitizer, 0.01-3 parts silicone additive, 0.001-5 parts surfactant, 0.001-5 parts tackifier and 200-900 parts solvent.
[0051] Preferably, the photoresist is a positive photoresist that can be exposed to 365 nm ultraviolet light.
[0052] It should be noted that the above-mentioned positive photoresist can be used to prepare the organic insulating layer in thin-film transistor liquid crystal displays (TFT-LCDs).
[0053] Preferably, the photosensitizer is selected from one or more of the following structures: , , , ; In the above photosensitizer structural formula, Ra is independently selected from OR e One of hydroxyl, alkyl, alkyl derivatives, phenyl and phenyl derivatives; R b R c R d Each is independently selected from one of hydrogen atom, C1-C6 alkyl, C1-C6 alkoxy, C4-C6 cycloalkyl, phenyl and phenyl derivatives; R e Independently selected from hydrogen and one of the following structures, .
[0054] Preferably, the surfactant is selected from one or more of fluorinated surfactants, organosilicon surfactants, and nonionic surfactants.
[0055] Preferably, the adhesive is selected from any one or more of the following: trimethoxysilylbenzoic acid, γ-methacryloyloxypropyltrimethoxysilane, vinyltriacetoxysilane, vinyltrimethoxysilane, γ-isocyanate propyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, N-phenylaminopropyltrimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0056] Preferably, the solvent is selected from: Ether solvents (e.g., ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dipropylene glycol dimethyl ether, tetrahydrofuran (THF), etc.); Monoethers and esters of ethylene glycol / diethylene glycol / propylene glycol (e.g., ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol methyl ether acetate PGMEA, propylene glycol diacetate, etc.); Ketone solvents (e.g., cyclohexanone, methyl isobutyl ketone, isophorone, etc.); Ester / lactone solvents (e.g., γ-butyrolactone GBL, benzyl acetate, ethyl benzoate, diethyl oxalate, diethyl maleate, ethyl carbonate, propylene carbonate, methyl 3-methoxypropionate, etc.); And one or more combinations of polar aprotic solvents (e.g., N,N-dimethylformamide DMF, N,N-dimethylacetamide, N-methyl-2-pyrrolidone NMP).
[0057] The beneficial effects of this invention are as follows: By chemically bonding photosensitive groups to polymer side chains, the photosensitivity of the resulting positive photoresist composition is superior to that prepared by physical blending. This invention, through the synergistic effect of specific monomer ratios and side chain structures, enables the photoresist to achieve a wider process window in 2.38% TMAH developer, with a development window exceeding 60 s. Furthermore, the positive photoresist composition provided by this invention exhibits a total mass loss of 5% (T0.05) in thermogravimetric analysis. d5% The temperature of each sample is above 276℃, the light transmittance is greater than 93%, the refractive index is not less than 1.53, and the dry etching resistance is less than 0.98 μm.
[0058] This invention limits the upper limit of alkyl / ester chain length (discarding long-chain monomers above C12) and the chain-side distribution density of polar functional groups that can be introduced into the side chains. This short, regular, and polarly balanced side-chain topology not only ensures the molecular-level dispersion and storage stability of the resin in ester / ether solvents and eliminates microscopic unevenness in coating thickness, but also avoids the weakening of chain packing density caused by long-chain plasticization, allowing the rigidity of the resin skeleton to be fully utilized, thereby fundamentally supporting high thermal stability (T0). d5% The simultaneous achievement of >276℃ and strong resistance to dry etching; and through matching the polymerization rate of specific monomers and controlling the feed, a statistical copolymer structure with uniform composition distribution was constructed, effectively eliminating the tendency of thermodynamic metastable phase separation caused by local long chain enrichment. Attached Figure Description
[0059] Figure 1 The image shows the infrared characterization of p-hydroxystyrene. Figure 2 The infrared characterization image of the photosensitive monomer PHS-PAC of Synthetic Example 1 is shown. Figure 3 Infrared characterization of the methacrylate copolymer of Synthetic Example 2; Figure 4 The image shows a gel chromatogram of the methacrylate copolymer from Synthetic Example 2. Detailed Implementation
[0060] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.
[0061] Unless otherwise specified, all raw materials used in the specific embodiments of the present invention are purchased from conventional commercial channels.
[0062] Synthesis Example 1: Preparation of the photosensitive monomer PHS-PAC 6 g of p-hydroxystyrene (PHS, Mr = 120.15 g / mol) and 13.53 g of 2-diazo-1-naphthol-5-sulfonyl chloride (Mr = 270.69 g / mol) were dissolved in 100 mL of DMF. 5.08 g of triethylamine (Mr = 101.6 g / mol) was added. The temperature of the reaction system was controlled at -10℃. After reacting for 2 h, the temperature was raised to 30℃ and the reaction was continued for 3 h. Oxalic acid was added to adjust the pH of the system to 5-6, and the mixture was filtered.
[0063] The filtrate was added dropwise to 1000 g of water to settle. After stirring for 2 h at room temperature, the mixture settled, filtered, and vacuum dried at 50 °C for 48 h to obtain the photosensitive monomer PHS-PAC.
[0064] The reaction process is shown in the figure below: .
[0065] Synthesis Example 2: Preparation of methacrylate copolymer 1 5 g of methacrylic acid (Mr=86.09), 9 g of hydroxyethyl methacrylate (Mr=130.14), 2 g of PHS-PAC (Mr=354.38), and 24 g of benzyl methacrylate (BzMA, Mr=176.21) were weighed and mixed, dissolved in PGMEA, and prepared into a solution with a solute content of 20 wt%. 2% (by mass) of AIBN initiator was added to the solution, and the reaction was carried out at 80 °C for 10 h under nitrogen protection. After the reaction was completed, the solution was poured into n-hexane to precipitate, filtered, and the solid was dried under vacuum at 40 °C for 24 h to obtain a pale yellow solid product. Its molecular weight (Mw) was 9070, acid value was 77.59 mgKOH / g, and dispersion (PDI) was 1.96.
[0066] Synthesis Example 3: Preparation of methacrylate copolymer 2 5 g of methacrylic acid (Mr=86.09), 5 g of hydroxyethyl methacrylate (Mr=130.14), 6 g of PHS-PAC (Mr=354.38), and 20 g of benzyl methacrylate (BzMA, Mr=176.21) were weighed and mixed, dissolved in PGMEA, and a solution with a solute content of 20 wt% was prepared. 1% AIBN initiator (based on the total monomer mass) was added to the solution, and the reaction was carried out at 80 °C for 5 h under nitrogen protection. After the reaction was completed, the solution was poured into n-hexane to precipitate the solid, filtered, and the solid was dried under vacuum at 40 °C for 48 h to obtain a pale yellow solid product. Its molecular weight (Mw) was 16426, acid value was 90.52 mgKOH / g, and PDI (partial dispersion index) was 2.56.
[0067] Synthesis Example 4: Preparation of methacrylate copolymer 3 The only difference between this synthesis example and synthesis example 2 is that: Replace benzyl methacrylate with an equimolar amount of methyl methacrylate; A pale yellow solid product was obtained. The molecular weight (Mw) of the product was 10523, the acid value was 81.46 mgKOH / g, and the dispersion (PDI) was 1.87.
[0068] Synthesis Example 5: Preparation of methacrylate copolymer 4 The only difference between this synthesis example and synthesis example 3 is that: Replace benzyl methacrylate with an equimolar amount of octyl methacrylate; A pale yellow solid product was obtained. The molecular weight (Mw) of the product was 15,500, the acid value was 78.58 mgKOH / g, and the dispersion (PDI) was 2.13.
[0069] Synthesis Example 6: Preparation of the photosensitive monomer HMS-PAC 7.5 g of 4-vinylguaiacol (HMS, Mr=150.17) and 13.53 g of 2-diazo-1-naphthol-5-sulfonyl chloride (Mr=270.69 g / mol) were dissolved in 150 mL of a mixed solvent of dioxane and acetone (volume ratio 1:1). 10 g of 20 wt% TMAH aqueous solution was added. The reaction system was controlled at 20 °C and reacted for 4 h. The temperature was raised to 80 °C and reacted for 3 h. Acetic acid was added to adjust the pH of the system to 5-6, and the mixture was filtered.
[0070] The filtrate was added dropwise to 1500 g of water, stirred for 2 h at room temperature, allowed to settle, filtered, and then vacuum dried at 40 °C for 72 h to obtain the photosensitive monomer HMS-PAC.
[0071] Synthesis Example 7: Preparation of methacrylate copolymer 5 The only difference between this synthesis example and synthesis example 2 is that: Replace PHS-PAC with an equimolar amount of HMS-PAC; Increase the amount of methacrylic acid to 10 g; The amount of AIBN initiator was adjusted to 3% of the total monomer mass; A pale yellow solid product was obtained. The molecular weight (Mw) of the product was 3200, the acid value was 139.14 mgKOH / g, and the dispersion (PDI) was 1.67.
[0072] Synthesis Example 8: Preparation of methacrylate copolymer 6 The only difference between this synthesis example and synthesis example 7 is that: Reduce the amount of methacrylic acid used to 2.5 g; Replace benzyl methacrylate with an equimolar amount of adamantane methacrylate; A pale yellow solid product was obtained. The molecular weight (Mw) of the product was 4500, the acid value was 43.45 mgKOH / g, and the dispersion (PDI) was 1.59.
[0073] Comparative Synthesis Example 1: Preparation of Methacrylate Copolymer 7 The only difference between this comparative synthesis example and synthesis example 2 is that: Replace benzyl methacrylate with an equimolar amount of lauryl methacrylate; A pale yellow solid product was obtained. The molecular weight (Mw) of the product was 10441, the acid value was 77.26 mgKOH / g, and the dispersion (PDI) was 1.82.
[0074] Examples and Comparative Examples of Positive Photoresist Compositions In the examples and comparative examples, the following reference numerals are used to represent the corresponding chemical substances: methacrylate copolymer A-1: Product of Synthetic Example 2; A-2: Product of Synthetic Example 3; A-3: Product of Synthetic Example 4; A-4: Product of Synthetic Example 5; A-5: Product of Synthetic Example 7; A-6: Product of Synthetic Example 8; Photoacid-producing agents B-1: condensate of 1,1,1-tris(p-hydroxyphenyl)ethane (1.0 mol) and 1,2-naphthoquinone diazido-5-sulfonyl chloride (1.0 mol); B-2: A condensate of 1,1,1-tris(p-hydroxyphenyl)ethane (1.0 mol) and 1,2-naphthoquinone diazido-5-sulfonyl chloride (2.0 mol); B-3: condensate of 1,1,1-tris(p-hydroxyphenyl)ethane (1.0 mol) and 1,2-naphthoquinone diazido-5-sulfonyl chloride (3.0 mol); <c>surfactants FZ-2122, DOWSIL™; <d>Adhesive γ-isocyanate propyltriethoxysilane, Shin-Etsu Chemical Industry Co., Ltd. <e>solvent E-1: Propylene glycol monomethyl ether acetate (20°C, 3.75 mmHg); E-2: Diethylene glycol dimethyl ether.
[0075] Example 1 100 g of the methacrylate copolymer (A-1) containing photosensitive monomers synthesized in Synthesis Example 2, 3 g of photoacid generator (B-3), 0.4 g of surfactant (C), and 0.6 g of adhesive (D) were added to a container. Then, solvent (E) was added to make the solute concentration 20 wt%, resulting in a positive photoresist composition.
[0076] Examples 2-10 and Comparative Examples 1-4: A positive photoresist composition and its preparation method Examples 2-10 and Comparative Examples 1-4 were prepared in the same manner as in Example 1, except that the types and amounts of each component were changed as shown in Tables 1 and 2.
[0077] Additionally, the <-> in Tables 1 and 2 indicates that the corresponding component was not used.
[0078] Furthermore, in Comparative Examples 1-2, the resin represented by formula (Ⅲ) (weight-average molecular weight 15000) was used instead of the resin in Example 1 above.< / e> < / d> < / c> The methacrylate copolymer shown was prepared using the same method as in Example 1, except that the composition and content of the positive photoresist composition varied according to the composition described in Table 2 below.
[0079]
[0080] III In equation (Ⅲ), p is 0.3, q is 0.2, and r is 0.5.
[0081] Table 1. Ingredients and Dosage of Examples 1-10
[0082] Table 2. Components and Dosage of Comparative Examples 1-4
[0083] Performance tests of the positive photoresist compositions provided in the experimental examples, embodiments, and comparative examples The positive photoresist compositions prepared using the above examples and comparative examples were evaluated for the following performance: (1) Evaluation of photosensitivity On a silicon substrate, the positive photoresist compositions obtained in Examples 1-10 and Comparative Examples 1-4 were spin-coated, and pre-baked at 100 °C for 2 min using a hot plate to form a coating film with a thickness of 2.5 μm. For the obtained coating film, a Canon PLA-501F exposure unit (ultra-high pressure mercury lamp) was used, with the silicon wafer placed under a mask having a 3.0 μm linewidth pattern, and the exposure time was 90 mJ / cm². 2 Exposure was performed at the specified exposure energy in a 2.38% (w / w) tetramethylammonium hydroxide (TMAH) solution at 25°C using a development time gradient experiment. The time at which a clear pattern first appeared (T1) and the time at which the pattern began to collapse, erode, or overdeveloped (T2) were observed and measured. The development window was calculated as T2 - T1. The performance results are shown in Tables 3 and 4.
[0084] The wider the window, the greater the process tolerance and the less sensitive it is to fluctuations in development time.
[0085] (2) Evaluation of refractive index A coating was formed on a glass substrate using the same coating conditions as described in the "Photosensitivity Evaluation" section above. The resulting films were then subjected to a cumulative irradiation of 1000 mJ / cm² using a Canon PLA-501F exposure lamp (ultra-high pressure mercury lamp). 2 After exposure, the film was heated at 230°C for 1 hour in a clean drying oven to obtain a cured film. The refractive index of the cured film was measured at 633 nm using an Auto EL IV NIR III spectrometer. When the refractive index is higher than 1.50, the material is considered suitable for use as an interlayer insulating film.
[0086] (3) Evaluation of heat resistance A silicon substrate with a cured film was prepared using the above-described "refractive index evaluation" method. The cured film was then peeled off the silicon substrate, and the thermogravimetric analysis (TGA) was used to measure the thermal weight loss of the cured film at 0-500℃. A total mass loss of 5% (T) was considered. d5% The temperature results at that time are shown in Tables 3 and 4.
[0087] (4) Evaluation of light transmittance Silicon substrates with the same cured film were prepared using the above-mentioned "refractive index evaluation" method. The transmittance of the glass substrate coated with this cured film was measured using a spectrophotometer "TU-1810" (manufactured by Beijing General Analytical Instrument Co., Ltd.) in the wavelength range of 400-800 nm. The results are shown in Tables 3 and 4. When the minimum transmittance exceeds 92%, the light transmittance is considered to be good.
[0088] (5) Evaluation of dry etching resistance Using the above-mentioned "refractive index evaluation" method, a cured film was formed on a silicon substrate. A dry etching apparatus CDE-80N (manufactured by Shibaura Mechatronics Co., Ltd.) was used with etching gas CF 450 mL / min, O2 10 mL / min, and output 400 mW. Dry etching was performed for 90 s. The film head before and after the treatment was measured. The results are shown in Tables 3 and 4. When the film thickness decreased by less than 1.0 μm, the dry etching resistance was considered good.
[0089] The results of the above experiments are shown in Tables 3 and 4 below: Table 3. Results of Experiments in Examples 1-10
[0090] Table 4. Results of Comparative Examples 1-4
[0091] From the results in Tables 3 and 4, it can be seen that, since the positive photoresist composition of this invention uses the methacrylate copolymer shown in Formula (II), the cured film of the obtained positive photoresist composition, compared with the cured films of the positive photoresist compositions formed by Comparative Examples 1-2 using polymer raw materials with the structure shown in Formula (III) in Table 4, shows that: this invention directly introduces specific photosensitive groups on the resin backbone and optimizes the chain-wise distribution density of polar functional groups in the polymer side chains. During the exposure process, the photosensitive groups on the resin side chains and the photosensitive agent in the system undergo a Wolff rearrangement reaction simultaneously. On the one hand, the reaction generates a large number of hydrophilic carboxyl groups in situ in the resin chain segments; on the other hand, the decomposition products of the photosensitive agent, which originally had anti-dissolution properties, are also transformed into strongly hydrophilic substances. This dual hydrophilization mechanism amplifies the solubility difference between the exposed and unexposed areas in the alkaline developer, significantly improving the development contrast. Thanks to this, this invention achieves a significant widening of the development process window, allowing the production line to perform development operations within a wider time tolerance, effectively avoiding pattern residue or bottom etching defects caused by process fluctuations, and greatly reducing mass production risks.
[0092] The development window of the cured film obtained in Comparative Examples 1-2 is ≤45 s; The cured film obtained in this embodiment of the invention has a development window ≥ 60 s; The cured film T obtained in Comparative Examples 1-2 d5% ≤258℃; The cured film T obtained in the embodiments of the present invention d5% ≥277℃; The cured films obtained in Comparative Examples 1 and 2 all had a light transmittance of 91%. The light transmittance of the cured films obtained in the embodiments of the present invention is ≥93%; The refractive index of the cured films obtained in Comparative Examples 1 and 2 was 1.51. The refractive index of the cured films obtained in the embodiments of the present invention is ≥1.53; The cured films obtained in Comparative Examples 1 and 2 all exhibited dry etching resistance > 1.4 μm; The cured films obtained in the embodiments of the present invention all exhibit dry etching resistance of less than 1.0 μm, demonstrating good dry etching resistance. It is evident that the cured film formed by the positive photoresist composition provided by the present invention has better performance than the cured film of the positive photoresist composition prepared by existing polymers, and has significant progress.
[0093] The polymer containing a photosensitive structure used in this invention possesses a stable and wide development window, good transparency, and is beneficial for improving the aperture ratio and water resistance of acrylate photoresists. The polymer containing the photosensitive structure of this invention exhibits good thermal stability, mechanical properties, and chemical properties, with a high Tg. d5% Temperature is also one of the key factors for achieving high-performance insulating film materials.
[0094] In Comparative Examples 3 and 4, it was found that the resin floated on top of the solvent during the preparation of the photoresist composition. After thorough mixing and shaking, a homogeneous and stable solution could be formed. This indicates that in the system of the present invention, when the resin of the photoresist composition uses ester monomers with more than C12, the polarity and density of the resin are significantly reduced, leading to a deterioration in the solubility parameter matching with conventional ester / ether-based photoresist solvents, forming a thermodynamically metastable system. The resulting phase separation tendency not only impairs the solution storage stability and coating uniformity, but also transmits the micro-inhomogeneity of the film composition to the spatial fluctuation of the development rate, thereby deteriorating the process window. At the same time, long-chain plasticization is also detrimental to thermal stability and etching resistance.
[0095] This invention effectively improves the adhesion between the resin and the matrix by adjusting the chain-linked distribution density of polar and non-polar functional groups in the resin formed by the highly photosensitive monomer and (meth)acrylic acid monomer. While maintaining a high residual film rate, pattern flatness, and aperture ratio, it significantly widens the development process window.
[0096] from Figure 1 , Figure 2 and Figure 3 It can be seen from this that at 1300 cm -1 The presence of a distinct -N=N absorption peak nearby indicates the introduction of a photosensitive structure into the polymer. This is based on the fact that the photosensitive properties of the product are mainly due to the Wolff rearrangement that occurs after the -N=N double bond absorbs ultraviolet light, thereby altering the difference in the resin's solubility in the developer before and after the process, ultimately forming the pattern.
[0097] Figure 4 The molecular weight spectrum of the methacrylate copolymer synthesized in Example 2 is given.
[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A methacrylate copolymer, characterized in that, The structure is shown in Equation I: Ⅰ In Formula I, X is an oxygen atom; R1 is a hydrogen atom; R2 is independently selected from one of carboxyl, C1-C8 alkyl, C1-C8 alkyl derivatives and phenyl; R3 is independently selected from one of C2-C8 alkyl groups, C2-C8 alkyl derivatives, adamantyl, phenyl, and benzyl groups; R4 is independently selected from either a hydrogen atom or a methyl group; R5 is independently selected from either hydrogen or methoxy groups; R6 is independently selected from one of the following structures: In terms of molar ratio, a:b:c = 0-1:0-1:0-1, and b and c are not 0.
2. The methacrylate copolymer according to claim 1, characterized in that, The methacrylate copolymer has a weight-average molecular weight of 2000-20000 and a dispersion of 1.0-3.
0.
3. The method for preparing the methacrylate copolymer according to claim 1 or 2, characterized in that, Includes the following steps: S1. Dissolve the copolymer monomer in propylene glycol monomethyl ether acetate to obtain a monomer solution; S2. Mix the monomer solution obtained in step S1 with the initiator to react and obtain the product to be separated; S3. Separate the product to be separated obtained in step S2 to obtain the methacrylate copolymer; The copolymer monomer is composed of a photosensitive monomer shown in Formula II, a monomer selected from one or more of ethyl methacrylate, propyl methacrylate, butyl methacrylate, pentyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl methacrylate, benzyl methacrylate, and adamantyl methacrylate, and a monomer selected from one or two of methacrylic acid and styrene; Ⅱ In Formula II, R1 is a hydrogen atom; X is an oxygen atom; R5 is independently selected from either hydrogen or methoxy groups; R6 is independently selected from one of the following structures, 。 4. The method for preparing the methacrylate copolymer according to claim 1 or 2, characterized in that, Includes the following steps: S1. Dissolve the copolymer monomer in propylene glycol monomethyl ether acetate to obtain a monomer solution; S2. Mix the monomer solution obtained in step S1 with the initiator to react and obtain the product to be separated; S3. Separate the product to be separated obtained in step S2 to obtain the methacrylate copolymer; The copolymer monomer is composed of a photosensitive monomer shown in Formula II and a monomer selected from one or more of the following: ethyl methacrylate, propyl methacrylate, butyl methacrylate, pentyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl methacrylate, benzyl methacrylate, and adamantyl methacrylate. Ⅱ In Formula II, R1 is a hydrogen atom; X is an oxygen atom; R5 is independently selected from either hydrogen or methoxy groups; R6 is independently selected from one of the following structures, 。 5. The use of the methacrylate copolymer according to claim 1 or 2 in the preparation of photoresist.
Citation Information
Patent Citations
A heat-resistant photoresist composition
CN108535960B
A pag key type photosensitive photoresist resin and a preparation method thereof
CN119930894B
Method for forming organic insulator of high aperture TFT-LCD using positive resist composition
KR1020040032468A
Photosensitive composition and hardened film
CN107608178A
Polymers and positive resist compositions
US6221989B1